Revisiting organizational credibility and organizational reputation – a situational crisis communication approach - Jamal, Jamilah; Abu Bakar, Hassan (EDP Sciences, 2017)
Organizational credibility, the extent of which an organization as the source of messages is perceived as trustworthy and reliable, is one important aspect to determine organization’s survival.The perceived credibility of the messages will either strengthen or worsen an organization reputation.The primary objective of this paper is to revisit the concept of organizational credibility and its interaction with organizational outcomes such as organizational reputation.Based on the situational crisis communication theory (SCCT), this paper focuses on the impact of organizational credibility on organizational reputation following a crisis. Even though the SCCT has been widely used in crisis communication research, the theory still has its own limitations in explaining factors that could potentially affect the reputation of an organization.This study proposes a model by integrating organizational credibility in the SCCT theoretical framework.Derived from the theoretical framework, three propositions are advanced to determine the relationships between organizational credibility with crisis responsibility and perceived organizational reputation.This paper contributes to further establishing the SCCT and posits key attributes in the organizational reputation processes..